Profesionalna načela v zdravstveni negi - Filej, Bojana (Obzornik zdravstvene nege, 2001)
The article describes different professional principles in nursing care which depend upon the development of the profession. Nursing care is becoming increasingly interesting as an economic category , scientific discipline, research category and as an element of the system of quality. In the article, professional principles of nursing care are presented from diferent aspects.
Keywords: medicinske sestre; zdravstvena nega